2018
DOI: 10.1175/jcli-d-17-0451.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tropical Precipitation on Summertime Euro-Atlantic Circulation via a Circumglobal Wave Train

Abstract: The influence of tropical precipitation variability on summertime seasonal circulation anomalies in the Euro-Atlantic sector is investigated. The dominant mode of the maximum covariance analysis (MCA) between the Euro-Atlantic circulation and tropical precipitation reveals a cyclonic anomaly over the extratropical North Atlantic, contributing to anomalously wet conditions over western Europe and dry conditions over eastern Europe and Scandinavia (in the positive phase). The related mode of tropical precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 58 publications
6
70
0
Order By: Relevance
“…In the eastern area, blocking events are preceded by a statistically significant low‐frequency wave train (Figure c). This is in good agreement with Schneidereit et al (), who showed that the 2010 blocking highs over Russia were associated with a low‐frequency wave train likely forced by a La Niña event in the tropical Pacific (see also O'Reilly et al, ). We go further by showing that this low‐frequency Rossby wave train was not only present during the 2010 events, as we obtain the same results when the blocking events of summer 2010 are removed (Figure S2 in the supporting information; the same holds for 2003 in the western area).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the eastern area, blocking events are preceded by a statistically significant low‐frequency wave train (Figure c). This is in good agreement with Schneidereit et al (), who showed that the 2010 blocking highs over Russia were associated with a low‐frequency wave train likely forced by a La Niña event in the tropical Pacific (see also O'Reilly et al, ). We go further by showing that this low‐frequency Rossby wave train was not only present during the 2010 events, as we obtain the same results when the blocking events of summer 2010 are removed (Figure S2 in the supporting information; the same holds for 2003 in the western area).…”
Section: Resultssupporting
confidence: 91%
“…Problems representing the large‐scale low‐frequency wave train forcing in general circulation models (e.g., O'Reilly et al, ) could lead to an underestimation of blocking events in the eastern area. This could explain the negative bias observed in twentieth century coupled runs from general circulation models from CMIP5 (see Figure 5 from Masato et al, ) at 30–50°E, 60°N.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Nonetheless, this study highlights the importance of evaluating the representation of the QBO – and its connection to the NAO – in operational seasonal forecasting systems. A similar signal‐to‐noise issue has been found in skilful seasonal forecasts of summertime European precipitation (Dunstone et al ) and the QBO is unlikely to be responsible for the signal‐to‐noise issue in these summer hindcasts; however, it could be that another relevant teleconnection mechanism, such as from the tropical Pacific (O'Reilly et al ), could be too weakly represented in these summer hindcasts. Nonetheless, the results of the present study suggest that seasonal forecasting models which capture predictable relationships too weakly may be able to exhibit substantial ensemble mean skill with a large number of ensemble members, but will have a signal that is somewhat too weak.…”
Section: Summary and Further Discussionsupporting
confidence: 60%
“…Understanding the predictability of extratropical circulation anomalies on seasonal time‐scales is essential for making better decisions in societal sectors that rely crucially on weather and climate information for the seasons to come. Whereas our forecast models' abilities to predict the evolution of tropical sea‐surface temperature (SST), especially in the El Niño–Southern Oscillation (ENSO) relevant Pacific Ocean, have improved over the recent decades and led to demonstrated skill (Weisheimer et al, ; Barnston et al, ), forecasting the extratropical tropospheric circulation variability remains a major challenge in seasonal prediction systems (Weisheimer et al, ; Lavers et al, ; Kim et al, ; Sigmond et al, ; Weisheimer and Palmer, ; Molteni et al, ; Befort et al, ; Beverley et al, ; O'Reilly et al, ).…”
Section: Introductionmentioning
confidence: 99%